'Always gotta be two mans': Lifers, risk, rehabilitation, and narrative labour. (January 2020) - Warr, Jason
All prisoners have their identity stripped from them and, ultimately, reconstructed by the institutions in which they are incarcerated. However, for life and indeterminately sentenced prisoners the effects of this process, reinforced over extended periods, creates a particular set of burdens. For it is this population, above and beyond that of other prisoners, who need to address the implications of an imposed carceral identity in both navigating the day-to-day life of the prison and securing release. The four core burdens are firstly, an ambiguity on what identity indeterminately sentenced prisoners were supposed to have. Secondly, reconciling an imposed identity that they did not necessarily feel adhered to their pre-established sense of self. Thirdly, recognition that in order to operate or perform within the prison they needed to adopt an institutionally acceptable form of their self. Fourthly, that they had to manage how their performance of self was judged and recorded by the prison. This article aims to contribute to the growing body of work on Narrative Criminology by arguing that these burdens results in what I define as narrative labour .